Bipolar Osteochondral Allograft Transplantation of the Patella and Trochlea. (October 2020) - Mirzayan, Raffy; Charles, Michael D.; Batech, Michael; Suh, Brian D.; DeWitt, David
Objective: To evaluate clinical, functional, and radiographic outcomes of patients who underwent bipolar osteochondral allograft transplantation (OCAT) of the patellofemoral joint (PFJ). Design: Prospectively collected data on 18 knees who underwent fresh osteochondral allograft transplantation of the patella and trochlea by a single surgeon were reviewed. Inclusion criteria were: high-grade chondral lesions of PFJ (5 knees), or recurrent patella dislocations with trochlear dysplasia and chondral injury to the patella and/or trochlea (13 knees). Functional scores were obtained preoperatively and at follow-up appointments included Knee injury and Osteoarthritis Outcome Score (KOOS), International Knee Documentation Committee (IKDC), Oxford, Cincinnati, Tenger-Lysholm, visual analogue scale (VAS)–pain, and Single Assessment Numeric Evaluation (SANE). Grafts were also evaluated using Osteochondral Allograft MRI Scoring System (OCAMRISS). Results: Three patients were lost to follow-up, leaving 4 knees in group 1, and 11 knees in group 2. Average age was 28.9 years (range 16-52 years). The average follow-up was 33.2 months (range 12-64 months). There was significant improvement of KOOS (from 38.7 to 83.1), IKDC (from 28.2 to 76.6), Tegner-Lysholm (from 38.3 to 88.3), Oxford (from 22.7 to 42.9), Cincinnati (from 35.1 to 83.6), VAS (from 71 to 17.9.), and SANE (from 43.3 to 83) ( P < 0.0001). The OCAMRISS score for patella was 2.23 and for trochlea 4.69. There were no revisions or conversions to arthroplasty Conclusion: Bipolar OCAT of the patella and trochlea provide significant improvement in functional outcomes, relief from pain, activity level, and prevent recurrent instability.